PELATIHAN PEMBUATAN PUPUK DAN KOMPOS BERBASIS BAHAN BAKU LOKAL DARI LIMBAH SAPI PEGON DI KELOMPOK TERNAK MALOWO JAYA SAMBENG KABUPATEN LAMONGAN MATERIALS FROM PEGON COW WASTE IN MALOWO JAYA LIVESTOCK GROUP, SAMBENG, LAMONGAN REGENCY - Wenny Ladhunka Nur Aliyya; Anik Fadlilah; Alfian Adi Atma; Edi Sutanto; M. Sulthonuddin; Febriani Aulia Adhawati; Rif’an Alfiani (Universitas Majalengka, 2022)
The purpose of this community service activity is to realize the utilization of livestock manure waste, so that there is no accumulation and environmental pollution, especially in the Malowo Jaya Sambeng livestock group as an initial pilot and additional income in the village. There are many problems faced by these livestock groups, including the lack of adequate feed for cattle, processing the waste produced, and marketing the results. So that an activity is needed to provide information on solving problems experienced through community service programs. Activities carried out in community service are providing direct counseling and training to farmers and the local community. The community service method is carried out with lectures and material presentation techniques, then continued discussions and training on making liquid fertilizers and solid fertilizers directly packaged in the form of offline workshops. This activity was warmly and enthusiastically welcomed by livestock groups and the local community which was marked by active discussions and enthusiasm in participating in the training from beginning to end in a series of activities carried out. The completion of this community service activity has more or less provided solutions to problems, especially in the processing of livestock waste in the cultivation of pegon cattle in the Malowo Jaya livestock group and most of the farmers in Kedungwangi village, Sambeng district, Lamongan regency.